Modulation of redox homeostasis: A strategy to overcome cancer drug resistance - Li, Yang; Zhang, Xiaoyue; Wang, Zhihan; Li, Bowen; Zhu, Huili (Frontiers in Pharmacology, 2023)
Cancer treatment is hampered by resistance to conventional therapeutic strategies, including chemotherapy, immunotherapy, and targeted therapy. Redox homeostasis manipulation is one of the most effective innovative treatment techniques for overcoming drug resistance. Reactive oxygen species (ROS), previously considered intracellular byproducts of aerobic metabolism, are now known to regulate multiple signaling pathways as second messengers. Cancer cells cope with evaluated amounts of ROS during therapy by upregulating the antioxidant system, enabling tumor therapeutic resistance via a variety of mechanisms. In this review, we aim to shed light on redox modification and signaling pathways that may contribute to therapeutic resistance. We summarized the molecular mechanisms by which redox signaling-regulated drug resistance, including altered drug efflux, action targets and metabolism, enhanced DNA damage repair, maintained stemness, and reshaped tumor microenvironment. A comprehensive understanding of these interrelationships should improve treatment efficacy from a fundamental and clinical research point of view.